2014
DOI: 10.3892/or.2014.3225
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib-associated matrix metalloproteinase suppression in p16-positive squamous cell carcinoma compared to HPV-negative HNSCC cells in vitro

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common type of cancer worldwide. The growth and invasion of HNSCC are strongly influenced by the extracellular matrix (ECM), which is modified by matrix metalloproteinases (MMPs). The MMP family is still relevant to cancer research, as it promotes malignant transformation, cell proliferation and modulation of angiogenesis even in the early stages of cancer. The proteolytic processing of bioactive molecules by MMP-14 (MT1-MMP) causes severe abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Besides that, it has been found that the activation of Wnt/β-catenin pathway can promote the progression of human cancers [ 15 ]. β-catenin belonging to the Wnt/β-catenin signaling pathway was reported to participate in tumorigenesis [ 16 ]. Wnt/β-catenin signaling pathways was also identified as therapeutic targets in cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, it has been found that the activation of Wnt/β-catenin pathway can promote the progression of human cancers [ 15 ]. β-catenin belonging to the Wnt/β-catenin signaling pathway was reported to participate in tumorigenesis [ 16 ]. Wnt/β-catenin signaling pathways was also identified as therapeutic targets in cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of c-kit during EMT remains unclear. Also known as cluster of differentiation (CD)117, c-kit is a member of the receptor tyrosine kinase family, and acts as oncogene in several tumours ( 19 ). Tang et al ( 20 ) have previously described an important function for c-kit in the progression of salivary adenoid cystic cancer by orchestrating EMT.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 MMPs are capable of ECM remodeling, favoring the invasion and proliferation of tumor cells. 38,39 MMPs have been detected in both cyst fluids and wall tissue extracts of various odontogenic cysts and odontogenic tumors, including ABs, suggesting that these enzymes play a key role in regulation of tumor and cyst growth. [40][41][42][43] In the present research, the expression of MMP in AB and its effect on tumor cell invasion and the prognosis of patients were varied.…”
Section: Discussionmentioning
confidence: 99%